2020
DOI: 10.1108/jocm-12-2018-0368
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy as a resource: a moderated mediation model of transformational leadership, extent of change and reactions to change

Abstract: PurposeDrawing from conservation of resources (COR) theory, this study empirically tests the impact of transformational leadership on commitment to and intention to support organizational change, proposing self-efficacy as a mediating mechanism. This study also aims to study whether the extent of change in the organization moderates the proposed relationship between transformational leadership, self-efficacy and change reactions.Design/methodology/approachA survey was conducted with a sample of 298 employees g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 70 publications
18
78
0
Order By: Relevance
“…Which ultimately leads them to manifest either compliance or even go beyond to engage in championing behavior as revealed in this study. The findings thus are in line with the tenet of conservation of resources theory (COR), which suggests that resources, mainly self-efficacy serve as instrumental in the face of organizational change (Bayraktar & Jimenez, 2019;Bayraktar & Jiménez, 2020).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Which ultimately leads them to manifest either compliance or even go beyond to engage in championing behavior as revealed in this study. The findings thus are in line with the tenet of conservation of resources theory (COR), which suggests that resources, mainly self-efficacy serve as instrumental in the face of organizational change (Bayraktar & Jimenez, 2019;Bayraktar & Jiménez, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…It has demonstrated that change-efficacy could also be an effective mechanism to facilitate the change of supportive behavior. Bayraktar and Jiménez (2020), in a recent study, also found changeefficacy as instrumental and lead to change-related outcomes such as commitment to change and intention to support change. It is also a significant determinant of change supportive behavior in a study conducted by (Shin et al, 2012).…”
Section: Discussionmentioning
confidence: 86%
“…Building on Bandura et al (1999) theory of self-efficacy, leader efficacy is a leader's confidence in his ability to lead others. Leaders must possess the necessary abilities to influence and motivate team members, which are important skills for implementing change effectively (Bayraktar and Jiménez, 2020). Leaders with high efficacy can accomplish organizational change goals because of their ability to overcome barriers.…”
Section: Methodsmentioning
confidence: 99%
“…Organizations may not employ an appropriate change model, and leaders may not possess the right leadership style to implement successful change initiatives (Lumbers, 2018). In addition, leaders may not have effective leader efficacy skills to steer the successful implementation of a change project (Bayraktar and Jiménez, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Yet much remains unclear about what exactly it means for these organizations to seek a sense of purpose to implement a holistic model of quality education (Srikanthan and Dalrymple, 2005). It is an enormous challenge for institutions to stay purposefully constant while also adapting their practices to the changing external requirements (Bayraktar, 2020; Maier, 2014). In view of such pressing concerns, this paper aims to examine the relationships between organizational purpose, leadership practices and sustainable outcomes for universities in emerging economies.…”
Section: Introductionmentioning
confidence: 99%